Islamic Professional Madrasa Teachers and Makarim Syari’ah in Teaching: A Phenomenological Approach - Syahraini Tambak; Firdaus Firdaus; Musaddad Harahap; Desi Sukenti; Muhammad Zaylani (AL-ISHLAH: Jurnal Pendidikan, 2023)
Extensive study has been conducted on professional educators, however, the integration of Islamic principles into their teaching practises has been overlooked. This study aims to determine Islamic professional madrasah teachers based on makarim syari’ah in the teaching profession. This study used a phenomenological research design involving 16 Aliyah madrasa teachers as informants. Data was collected by conducting interviews with madrasa teachers and analyzed using a systematic design. This research shows that professional teachers based on makarim syari’ah as an act that draws closer to the attributes of God, have commendable qualities such as wisdom, kindness, generosity, knowledge and forgiveness. Islamic professional madrasa teacher in the context of makarim syari’ah, anyone who has God's attributes, such as hikma, jud, hilm. 'ilm and 'awf, even though the attributes of Allah SWT. This is far nobler than His qualities that exist in humans. Commendable qualities are the main glue for teachers in carrying out the teaching profession to achieve success in learning. The teaching profession is not only used to teach humans but to bring himself to be a pious human being in the sight of Allah SWT. This is especially relevant for madrasa teachers, as it is a central part of the future madrasa teaching profession to promote their Islamic profession and build a generation of morals and dignity in the future.